Battery positive electrode sheet and preparation method thereof and battery

By passivating the poor areas of the active material layer of the battery positive electrode sheet, the passivation material in the composite layer and the passivation layer is used to suppress the electrolyte infiltration and the detachment of lithium ions, solving the lithium evolution and material dropping problems caused by uneven thickness of the battery electrode sheet, and improving the circulation and safety performance of the battery.

CN115249812BActive Publication Date: 2025-04-15SHENZHEN BYD LITHIUM BATTERY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110464282.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-27
Publication Date
2025-04-15
Estimated Expiration
2041-04-27

AI Technical Summary

Technical Problem

During the preparation of the battery electrode sheet, the thickness of the active material layer formed by the batch coating method is uneven, resulting in lithium decomposition and material dissipation of the electrode sheet, which affects the long-term use of the battery.

Method used

By passing the poor areas of the active material layer, a passivation area is formed, and the passivation materials (such as polyethylene glycol and its derivatives) in the composite layer and the passivation layer are used to inhibit the electrolyte infiltration and the detachment of lithium ions.

Benefits of technology

It effectively improves the structural stability of the battery positive electrode sheet, inhibits the precipitation of lithium dendrites from the negative electrode, improves the cycle performance and safety performance of the battery, and does not affect the energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115249812B_ABST
    Figure CN115249812B_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode sheet for a battery, comprising a current collector and an active material layer disposed on the surface of the current collector; the active material layer comprises an active region and a passivation region located on opposite sides of the active region along a first direction; the active region comprises an active material; the passivation region comprises a passivation material and an active material, and the passivation material comprises one or more of metal aluminum, metal nickel and stainless steel. The positive electrode sheet for the battery has good structural stability, is not easy to drop, and can effectively suppress lithium deposition in the battery. Using it in a battery can effectively improve the cycle performance and safety performance of the battery, and will not affect the energy density of the battery, thereby ensuring that the battery has excellent electrochemical performance. The present application also provides a method for preparing the above-mentioned positive electrode sheet for the battery and a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery positive electrode sheet and a preparation method thereof, and a battery. Background Art

[0002] In the process of preparing battery pole pieces, intermittent coating is often used to prepare battery pole pieces because blank current collectors need to be reserved for welding pole ears. However, the thickness of the active material layer formed by the intermittent coating method is not uniform at the edge. The uneven thickness of the active material layer will cause lithium deposition and material loss in the pole piece, which is not conducive to the long-term use of the battery.

[0003] In order to reduce the impact of uneven thickness of the active material layer on the battery, the current method is to apply tape to the edge of the active material layer to inhibit lithium deposition and material loss in the battery. However, the adhesive in the tape easily diffuses into the electrolyte, reducing the performance of the battery; and after multiple charge and discharge cycles of the battery with the positive electrode taped, a large number of lithium dendrites will still precipitate on the negative electrode surface corresponding to the taped position. The formed lithium dendrites will reduce the battery safety performance on the one hand, and on the other hand, it will lead to a decrease in battery capacity and a decrease in battery cycle performance, which is not conducive to the use of the battery. Summary of the invention

[0004] In view of this, the present application provides a battery positive electrode sheet, which has good structural stability, is not easy to fall off, and can effectively inhibit lithium plating at the battery negative electrode. Applying it in a battery can effectively improve the battery's cycle performance and safety performance, and will not affect the battery's energy density, thereby ensuring that the battery has excellent electrochemical properties.

[0005] In a first aspect, the present application provides a positive electrode sheet of a battery, comprising a current collector and an active material layer arranged on the surface of the current collector; the active material layer comprises an active region and a passivation region located on opposite sides of the active region along a first direction; the active region comprises an active material; the passivation region comprises a composite layer and a passivation layer, the composite layer comprises the active material and a passivation material mixed with the active material; the passivation layer comprises the passivation material, and the passivation material comprises one or more of polyethylene glycol and polyethylene glycol derivatives.

[0006] At present, when the intermittent coating method is used to coat the active material layer on the surface of the current collector, since the machine adopts segmented coating, the thickness of the active material layer formed by the machine at the start and end of coating is not uniform, which leads to unstable structure of the active material layer, easy material falling, and easy lithium dendrites in the negative electrode. The area with uneven thickness is the bad area. The battery positive electrode sheet of the present application forms a passivation area by passivating the bad area of ​​the active material layer. The passivation material in the passivation area can inhibit the infiltration of the electrolyte and the release of lithium ions in the active material, thereby reducing the kinetic capacity of the active material in the bad area, thereby improving the phenomenon of lithium dendrites formed by lithium precipitation in the negative electrode opposite to the passivation area, and effectively improving the structural stability of the positive electrode.

[0007] Optionally, the passivation region includes an active layer disposed on the surface of the current collector and a passivation layer disposed on the surface of the active layer; the active layer includes the active material, and the passivation layer includes the passivation material.

[0008] Optionally, the passivation layer has a thickness of 0.5 μm-95 μm.

[0009] Optionally, the active layer has a thickness of 10 μm-200 μm.

[0010] Optionally, the thickness ratio of the passivation layer to the active layer is 1:(0.1-400).

[0011] Optionally, the active layer includes a diffusion layer located on one side of the passivation layer, and the diffusion layer includes the active material and the passivation material.

[0012] Optionally, in the diffusion layer, the mass percentage of the passivation material shows a decreasing trend along the direction from the passivation layer to the active layer.

[0013] Optionally, the density of the passivation layer is greater than the density of the active layer.

[0014] Optionally, the width of the passivation area along the first direction is 3 mm-2 cm.

[0015] Optionally, the active material comprises a material capable of reversibly extracting and inserting lithium ions.

[0016] Optionally, the active material includes LiFePO4, Li3V2(PO4)3, LiMn2O4, LiMnO2, LiNiO2, LiCoO2, LiVPO4F, LiFeO2 or Li 1+x L 1-y-z M y N zOne or more of O2, wherein -0.1≤x≤0.2, 0≤y≤1, 0≤z≤1, 0≤y+z≤1.0, and L, M, and N are selected from Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Mg, and Ga, respectively.

[0017] Optionally, the active area further includes a conductive agent and a binder.

[0018] Optionally, the passivation region further includes the conductive agent and the adhesive.

[0019] Optionally, the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide, polyacrylonitrile and polyacrylate.

[0020] Optionally, the conductive agent includes one or more of acetylene black, carbon black, carbon nanotubes, carbon nanofibers, activated carbon and graphene.

[0021] Optionally, the mass percentage of the passivation material in the passivation area is 2%-40%.

[0022] Optionally, the mass percentage of the active material in the passivation region is 25%-97.8%.

[0023] Optionally, the mass percentage of the binder in the passivation area is 0.1%-15%.

[0024] Optionally, the mass percentage of the conductive agent in the passivation region is 0.1%-20%.

[0025] Optionally, the thickness of the current collector is 5 μm-100 μm. Further, the thickness of the current collector is 8 μm-20 μm.

[0026] Optionally, the active material layer has a thickness of 10 μm-200 μm.

[0027] The battery positive electrode sheet provided in the first aspect of the present application forms a passivation area by passivating the bad area. The passivation layer in the passivation area can effectively block the electrolyte and inhibit the electrolyte from infiltrating the passivation area, thereby reducing the escape and migration rate of lithium ions in the passivation area, thereby solving the problem of lithium deposition at the negative electrode position corresponding to the passivation area, thereby improving the cycle performance and safety performance of the battery.

[0028] In a second aspect, the present application provides a method for preparing the above-mentioned battery positive electrode sheet, comprising the following steps:

[0029] Providing a current collector, coating a surface of the current collector with an active material layer to be passivated; the active material layer to be passivated includes an active region and regions to be passivated located on opposite sides of the active region along the first direction;

[0030] The passivation material is covered on the area to be passivated, and the active material layer to be passivated is rolled to form a passivation area to obtain the positive electrode sheet of the battery; the passivation material includes one or more of metal aluminum, metal nickel and stainless steel;

[0031] Optionally, the passivation material includes one or more of metal aluminum, metal nickel and stainless steel.

[0032] Optionally, the passivation material has a thickness of 2 μm-100 μm.

[0033] Optionally, the rolling pressure is 1Mpa-10Mpa.

[0034] The preparation method of the battery positive electrode sheet provided in the present application has a simple and controllable process, is easy to operate, is conducive to realizing automated production, and the obtained battery positive electrode sheet has good structural stability. Applying it in a battery can make the battery have good cycle performance and safety performance.

[0035] In a third aspect, the present application provides a battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode, wherein the positive electrode comprises the battery positive electrode sheet described in the first aspect of the present application or the battery positive electrode sheet obtained by the preparation method described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a schematic diagram of the battery structure;

[0037] Figure 2 A top view of a coated electrode prepared by an intermittent coating method;

[0038] Figure 3 This is a front view of a coated electrode prepared by an intermittent coating method;

[0039] Figure 4 Schematic diagram of bad areas of electrodes in a battery;

[0040] Figure 5 A top view of a positive electrode sheet of a battery provided in one embodiment of the present application;

[0041] Figure 6 A front view of a positive electrode sheet of a battery provided in one embodiment of the present application;

[0042] Figure 7 A schematic diagram of the passivation region layer structure provided in one embodiment of the present application. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0044] See also Figure 1 , Figure 1 The figure is a schematic diagram of the battery structure. The core components of the battery include the positive electrode sheet 10, the negative electrode sheet 20, the separator 30 and the electrolyte 40 as well as the corresponding connecting accessories and circuits. In the related art, since a blank area must be reserved on the current collector for welding the pole lugs, an intermittent coating method is often used to coat the active material layer to obtain the coated pole sheet, and then the coated pole sheet is cut and rolled to obtain the battery pole sheet. The intermittent coating method is to coat a section of slurry on the surface of the current collector and leave a blank section before coating the next section of slurry. Please refer to Figure 2 , Figure 2 The top view of the coated electrode sheet prepared by the intermittent coating method. The active material layer 102 is arranged on the surface of the current collector 101 at intervals, and the current collector 101 has an interval of blank areas. When the intermittent coating method is used, the thickness of the active material layer formed by the machine at the start and end of coating is not uniform, and the thickness at the edge of the active material layer will be greater. Please refer to Figure 3 , Figure 3 This is the front view of the coated electrode prepared by the intermittent coating method. Figure 3 In the embodiment, the thickness of the edge region of the active material layer 102 along the coating direction is greater than that of the middle region, and the thicker region is the defective region of the positive electrode sheet of the battery.

[0045] During the use of the battery, since there are more active materials in the bad area of ​​the positive electrode, the lithium ion concentration in the bad area of ​​the positive electrode will be higher during the battery charging process, and the corresponding lithium ion concentration in the negative electrode area will also be higher, which makes it easy for lithium dendrites to form in this area of ​​the negative electrode. Figure 4 , Figure 4 Schematic diagram of the bad area of ​​the electrode in the battery. Figure 4In the figure, area a represents the bad area with high lithium ion concentration in the positive electrode of the battery, that is, area a is the bad area with thick positive active material layer, and area b is the area of ​​the negative electrode of the battery corresponding to area a. After long-term use of the battery, area b is very likely to produce a large number of lithium dendrites. The hazards of lithium dendrites are mainly in three aspects: first, they will puncture through the diaphragm to cause short circuits, causing serious safety accidents; second, lithium dendrites can react with the electrolyte in situ to form an electronic insulation film on the surface, which will cause mutual electronic insulation between lithium dendrites. Once the root system is broken, the entire lithium dendrite loses its electrochemical activity, resulting in a rapid decrease in battery capacity; third, the spatial volume of lithium dendrites is large, which is easy to cause battery volume expansion and battery cycle performance attenuation. In addition, the bad area of ​​the active material layer of the positive electrode is also prone to material shedding, which is not conducive to the battery's cycle performance and safety performance.

[0046] To solve the above problems, the relevant technology is to stick tape on the edge of the active material layer coating. However, the tape contains polyurethane adhesives, and the main components are polyisocyanates, polyethers, alcohols, etc. The above components are easy to diffuse into the electrolyte, which is not conducive to the electrochemical properties and safety performance of the battery. In addition, after multiple charge and discharge cycles of the battery with positive electrode glue, the negative electrode position corresponding to the tape will still have relatively serious lithium dendrite precipitation, which cannot solve the problem well.

[0047] In order to improve the electrochemical performance and safety performance of the battery, the present application provides a battery positive electrode sheet, which passivates the undesirable areas with high lithium ion concentration, inhibits the infiltration of the electrolyte into the passivated area, slows down the escape rate of lithium ions, thereby effectively inhibiting the formation of lithium dendrites, and at the same time improves the structural stability of the battery positive electrode sheet. Applying it in the battery can effectively enhance the battery's cycle performance and safety performance.

[0048] See also Figure 5 , Figure 5 A top view of a positive electrode sheet of a battery provided in one embodiment of the present application. Figure 5 In the embodiment, the positive electrode sheet 10 of the battery includes a current collector 101 and an active material layer 102 disposed on the surface of the current collector 101; the active material layer 102 includes an active region c and a passivation region d; the passivation region d is located on two opposite sides of the active region c along the first direction. For further explanation of the position of the passivation region of the present application, please refer to Figure 6 , Figure 6 This is a front view of a positive electrode sheet of a battery provided in one embodiment of the present application. Figure 6In the invention, the active material layer 102 includes an active region c and a passivation region d located on opposite sides of the active region c along a first direction. In the present application, the first direction refers to a direction parallel to the coating direction of the battery pole piece. Since the battery pole piece is coated in sections, the thickness of the edge portion of the active material layer along the coating direction is relatively thick. The present application can effectively solve the problem caused by the uneven thickness of the active material by passivating the above-mentioned region. It can be understood that in the present application, the shape of the active material layer is a rectangle, the shape of the active region is a rectangle, and the two opposite sides of the active region are parallel to the first direction, and the other two opposite sides of the active region are perpendicular to the first direction; the shape of the passivation region is a rectangle, and the two opposite sides of the passivation region are parallel to the first direction, and the other two opposite sides of the passivation region are perpendicular to the first direction.

[0049] In the embodiments of the present application, the active region includes an active material, and the active material refers to a material that can reversibly release and embed lithium ions. In the present application, there is no special limitation on the active material, and the active material can be any active material known in the art. In some embodiments of the present application, the active material includes LiFePO4, Li3V2(PO4)3, LiMn2O4, LiMnO2, LiNiO2, LiCoO2, LiVPO4F, LiFeO2 or Li 1+x L 1-y-z M y N z One or more of O2, wherein -0.1≤x≤0.2, 0≤y≤1, 0≤z≤1, 0≤y+z≤1.0, and L, M, and N are selected from Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Mg, and Ga, respectively.

[0050] In an embodiment of the present application, the passivation region includes a passivation material and an active material, and the passivation material includes one or more of metal aluminum, metal nickel and stainless steel. The above-mentioned passivation material can block the pores between the active materials, making it difficult for the electrolyte to infiltrate, thereby inhibiting the escape of lithium ions, and the above-mentioned passivation material has good stability and has no effect on the performance of the battery. In some embodiments of the present application, metal aluminum is used as the passivation material. Metal aluminum has excellent ductility and can be in close contact with the active material layer in the passivation region of the positive electrode of the battery, thereby achieving effective passivation.

[0051] In the embodiment of the present application, the passivation region includes an active layer disposed on the surface of the current collector and a passivation layer disposed on the surface of the active layer; the active layer includes an active material, and the passivation layer includes a passivation material. Figure 7 , Figure 7 A schematic diagram of the passivation region layer structure provided in one embodiment of the present application. Figure 7In the embodiment, the passivation region includes an active layer B and a passivation layer A disposed on the surface of the active layer B. In the present application, by disposing a passivation layer on the surface of the bad area of ​​the positive electrode sheet of the battery, the passivation region can be isolated from the electrolyte, so that the lithium ions in the passivation region are difficult to diffuse into the electrolyte. In some embodiments of the present application, the active layer includes a permeation layer close to one side of the passivation layer, and the permeation layer includes an active material and a passivation material. In the present application, the thickness of the permeation layer is related to the passivation process and the passivation material. The thickness of the permeation layer may be equal to the thickness of the active layer or may be less than the thickness of the active layer. In the embodiment of the present application, along the direction from the passivation layer to the active layer, the mass percentage of the passivation material in the permeation layer shows a decreasing trend. After the electrode is rolled, the passivation material will further penetrate into the active material layer of the passivation region to form a permeation layer, thereby blocking the pores between the active materials and making it difficult for the electrolyte to infiltrate, thereby reducing the rate of lithium ion release in the bad area and reducing the risk of lithium plating at the negative electrode.

[0052] In the embodiment of the present application, the thickness of the passivation layer is 0.5μm-95μm, wherein the thickness of the passivation layer refers to the maximum thickness of the passivation layer. The thickness of the passivation layer may be, but is not limited to, 0.5μm, 5μm, 10μm, 20μm, 25μm, 30μm, 35μm, 40μm, 60μm, 80μm or 95μm. The use of a passivation layer of the above thickness can effectively isolate the electrolyte and inhibit the electrolyte from infiltrating the passivation area, thereby reducing the rate of lithium ion release in the passivation area. In the embodiment of the present application, the density of the passivation layer is greater than the density of the active layer. In the present application, the higher the density of the passivation layer, the more conducive it is to prevent the electrolyte from infiltrating the passivation area, thereby achieving a good passivation effect.

[0053] In the embodiment of the present application, the thickness of the active layer is 10 μm-200 μm. The thickness of the active layer can be, but is not limited to, 10 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 60 μm, 80 μm or 200 μm. In the embodiment of the present application, the thickness ratio of the passivation layer to the active layer is 1:(0.1-400). The thickness ratio of the passivation layer to the active layer can be, but is not limited to, 1:0.1, 1:5, 1:10, 1:50, 1:100 or 1:400.

[0054] In an embodiment of the present application, the width of the passivation region along the first direction is 1 mm-2 cm. In some embodiments of the present application, the width of the passivation region along the first direction is 3 mm-1.2 cm. The width of the passivation region along the first direction may be, but is not limited to, 1 mm, 3 mm, 5 mm, 7 mm, 1 cm, 1.2 cm or 2 cm. Within the above width range, the passivation region can effectively cover the bad area of ​​the electrode, thereby alleviating the problem of negative electrode lithium plating.

[0055] In the implementation manner of the present application, the active region also includes a conductive agent and a binder, and the passivation region also includes a conductive agent and a binder. In the present application, the binder and the conductive agent are not particularly limited, and the binder and the conductive agent can be any binder and conductive agent known in the art. In some implementation manners of the present application, the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polyamide, polyacrylonitrile and polyacrylate. In some implementation manners of the present application, the conductive agent includes one or more of acetylene black, carbon black, carbon nanotubes, carbon nanofibers, activated carbon and graphene.

[0056] In the embodiment of the present application, the mass percentage of the passivation material in the passivation region is 2%-40%. The mass percentage of the passivation material in the passivation region may be, but is not limited to, 2%, 5%, 10%, 25% or 40%. In the embodiment of the present application, the mass percentage of the active material in the passivation region is 25%-97.8%. The mass percentage of the active material in the passivation region may be, but is not limited to, 25%, 60%, 75%, 90%, 95% or 97.8%.

[0057] In the embodiment of the present application, the mass percentage of the binder in the passivation region is 0.1%-15%. The mass percentage of the binder in the passivation region can be, but not limited to, 0.1%, 0.5%, 1%, 2%, 5%, 7%, 10% or 15%. In the embodiment of the present application, the mass percentage of the conductive agent in the passivation region is 0.1%-20%. The mass percentage of the conductive agent in the passivation region can be, but not limited to, 0.1%, 0.5%, 1%, 2%, 5%, 10%, 15% or 20%.

[0058] In an embodiment of the present application, the thickness of the active material layer is 10 μm-200 μm. The thickness of the active material layer may be, but is not limited to, 10 μm, 20 μm, 50 μm, 100 μm, 150 μm or 200 μm. In an embodiment of the present application, the thickness of the current collector is 5 μm-100 μm. In some embodiments of the present application, the thickness of the current collector is 8 μm-20 μm. The thickness of the current collector may be, but is not limited to, 5 μm, 10 μm, 20 μm, 50 μm, 70 μm, 90 μm or 100 μm.

[0059] The battery positive electrode sheet provided in the present application effectively prevents the infiltration of electrolyte and the transmission of lithium ions in the poor area of ​​the positive electrode by passivating the positive electrode, thereby achieving the purpose of hindering the escape of lithium ions in the area, alleviating the problem of lithium plating at the negative electrode, and effectively improving the structural stability of the battery positive electrode sheet.

[0060] The present application also provides a method for preparing the above-mentioned battery positive electrode sheet, comprising the following steps:

[0061] Step 100: providing a current collector, and coating a surface of the current collector to form an active material layer to be passivated, wherein the active material layer to be passivated includes an active region and regions to be passivated located on opposite sides of the active region along a first direction;

[0062] Step 200: Covering the area to be passivated with a passivation material, and rolling the passivated active material layer to obtain a positive electrode sheet of a battery.

[0063] In step 100 of the present application, the first direction is parallel to the coating direction. The active material layer to be passivated can be formed by coating the surface of the current collector using any preparation method known in the art. In the embodiment of the present application, the active material layer to be passivated is formed by coating using an intermittent coating method, and the drying temperature after coating is 50°C-150°C.

[0064] In step 200 of the present application, the passivation material includes one or more of metal aluminum, metal nickel and stainless steel. Specifically, the passivation material can be metal powder or metal foil. Taking the passivation material as metal foil as an example, the metal foil is covered on the surface of the area to be passivated and then rolled on the area to be passivated. During the rolling process, the metal foil is tightly pressed on the surface of the active material layer to form a passivation layer.

[0065] In some embodiments of the present application, the passivation material includes one or more of aluminum foil, nickel foil and stainless steel foil. Using metal foil as a passivation material can better control the size of the passivation area. In the present application, when metal foil is used as a passivation material, the thickness of the metal foil is 2μm-100μm. The thickness of the metal foil can be, but is not limited to, 2μm, 5μm, 10μm, 20μm, 25μm, 30μm, 35μm, 40μm, 60μm, 80μm or 100μm. In some embodiments of the present application, the thickness of the metal foil is 20μm-40μm. When the thickness of the metal foil is 20μm-40μm, the prepared battery positive electrode sheet can have good structural stability, and the lithium ions in the poor positive electrode area are difficult to escape, thereby reducing the risk of lithium dendrite precipitation in the corresponding negative electrode area.

[0066] In the present application, rolling the active material layer to be passivated refers to rolling the entire active material layer to be passivated, that is, the rolling position includes the active area and the area to be passivated. In the embodiment of the present application, the rolling pressure is 1Mpa-10Mpa. The rolling pressure can be specifically but not limited to 1Mpa, 3Mpa, 5Mpa or 10Mpa. Under the above pressure range, the passivating material can be effectively rolled into the passivation area, thereby forming a passivation layer on the surface of the active layer in the passivation area. The passivating material will also penetrate into the active layer during the rolling process and form a penetration layer in the active layer, making it difficult for lithium ions in the passivation area to escape.

[0067] The present application also provides a lithium-ion battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode, wherein the positive electrode includes the battery positive electrode sheet provided in the present application.

[0068] In the present application, the negative electrode of the lithium-ion battery can be any negative electrode known in the art. In the embodiment of the present application, the negative electrode may include one or more of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, a lithium negative electrode, a sodium negative electrode, a potassium negative electrode, a magnesium negative electrode, a zinc negative electrode and an aluminum negative electrode. Among them, the carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, etc.; the silicon-based negative electrode may include silicon, silicon carbon, silicon oxygen, silicon metal compounds, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy. The lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy and a lithium indium alloy. In some embodiments of the present application, the current collector of the negative electrode is a copper foil, which can be a porous structure or a common copper foil, and the thickness of the copper foil is 5μm-100μm, and further, the thickness of the copper foil is 10μm-20μm; the negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon, lithium titanate, iron oxide, lithium titanium phosphate, titanium dioxide, silicon, silicon oxide, aluminum, tin and antimony; the binder includes one or more of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC) and styrene butadiene latex (SBR); the conductive agent includes one or more of acetylene black, Ketjen black, Super-P, carbon nanotubes, carbon nanofibers, activated carbon and graphene. In the present application, the preparation method of the negative electrode can adopt any method known in the art.

[0069] In the present application, the separator of the lithium-ion battery can be any separator known to those skilled in the art, for example, the separator can be one or more of polyolefin microporous membrane, polyethylene terephthalate, polyethylene felt, glass fiber felt or ultrafine glass fiber paper.

[0070] In the present application, the electrolyte of the lithium ion battery includes a solution of an electrolyte lithium salt in a non-aqueous solvent. In an embodiment of the present application, the electrolyte lithium salt includes lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorosilicate (LiSiF6), lithium tetraphenylborate (LiB(C6H5)4), lithium chloride (LiCl), lithium bromide (LiBr), lithium chloroaluminate (LiAlCl4), lithium fluoroalkylsulfonate (LiC(SO2CF3)3), LiCH3SO3, LiN(SO2CF3)2 and LiN(SO2C2F5)2. In some embodiments of the present application, the non-aqueous solvent includes one or more of a chain acid ester and a cyclic acid ester. In some embodiments of the present application, the chain acid ester includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC) and dipropyl carbonate (DPC). In some embodiments of the present application, the chain acid ester includes chain organic esters containing fluorine, sulfur or unsaturated bonds. In some embodiments of the present application, the cyclic acid ester includes one or more of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), γ-butyrolactone (γ-BL) and sultone. In some embodiments of the present application, the cyclic acid ester includes cyclic organic esters containing fluorine, sulfur or unsaturated bonds. In some embodiments of the present application, the non-aqueous solvent includes one or more of chain ethers and cyclic ether solutions. In some embodiments of the present application, the cyclic ether includes one or more of tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-MeTHF), 1,3-dioxolane (DOL) and 4-methyl-1,3-dioxolane (4-MeDOL).

[0071] In some embodiments of the present application, the cyclic ether includes a fluorine-containing, sulfur-containing or unsaturated bond-containing cyclic organic ether. In some embodiments of the present application, the chain ether includes one or more of dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), 1,2-dimethoxypropane (DMP) and diethylene glycol dimethyl ether (DG).

[0072] In some embodiments of the present application, the chain ether includes a chain organic ether containing fluorine, sulfur or unsaturated bonds. In some embodiments of the present application, the concentration of the electrolyte lithium salt in the electrolyte is 0.1 mol / L-15 mol / L. In some embodiments of the present application, the concentration of the electrolyte lithium salt is 1 mol / L-10 mol / L.

[0073] In the embodiments of the present application, the battery can be prepared by using either a lamination process or a winding process. In some embodiments of the present application, the battery is prepared by using a lamination process.

[0074] The lithium-ion battery provided in the present application has good cycle performance and safety performance due to the use of the battery positive electrode sheet of the present application.

[0075] The present application also provides a power vehicle, which includes the above-mentioned lithium-ion battery.

[0076] The technical solution of the present application is further described below with reference to a number of embodiments.

[0077] Example 1

[0078] 1) Preparation of battery positive electrode:

[0079] Weigh 1kg of positive electrode active material (LiCoO2), 20g of conductive agent (carbon nanotubes) and 20g of binder (vinylidene fluoride, PVDF) and add them to 1kg of N-methylpyrrolidone, stir in a mixer for 30 minutes to form a stable and uniform slurry; evenly coat the slurry on the surface of the current collector aluminum foil, put it in an oven and dry it at 80°C to obtain an active material layer; cover the 1cm area at the edge of the active material layer with a passivation material, which is a 10μm aluminum foil, so that the aluminum foil completely covers the area with uneven thickness of the active material layer, and press the active material layer with a pressure of 2Mpa to obtain a battery positive electrode sheet, and spot weld the pole ear to obtain a battery positive electrode. The thickness of the active material layer of the obtained battery positive electrode is 95μm, that is, the thickness of the active area in the active material layer is 95μm.

[0080] 2) Preparation of battery negative electrode:

[0081] Weigh 1 kg of negative electrode active material (composite negative electrode material of natural graphite and artificial graphite with a particle size of 15 μm, and the mass ratio of natural graphite to artificial graphite is 1:9), 10 g of conductive agent (acetylene black), and binder (30 g of styrene-butadiene rubber, 20 g of sodium carboxymethyl cellulose) and add them to 1 kg of deionized water. After stirring, coating, drying, rolling, and spot welding the pole ears, the battery negative electrode is obtained.

[0082] 3) Preparation of batteries:

[0083] The battery positive electrode, battery negative electrode and polyolefin microporous membrane separator prepared above were wound into a battery core, and after packaging, 1 mol / L lithium hexafluorophosphate electrolyte (solvent is 1:1:1 EC:DMC:DPC) was injected to obtain a battery. The battery of Example 1 was named DS-1.

[0084] Example 2

[0085] The difference from Example 1 is that the passivation material in Example 2 is a 30 μm thick aluminum foil. The battery of Example 2 is named DS-2.

[0086] Example 3

[0087] The difference from Example 1 is that the passivation material in Example 3 is 50 μm thick aluminum foil. The battery of Example 3 is named DS-3.

[0088] Example 4

[0089] The difference from Example 1 is that the passivation material in Example 4 is a nickel foil with a thickness of 10 μm. The battery of Example 4 is named DS-4.

[0090] Example 5

[0091] The difference from Example 1 is that the passivation material in Example 5 is a stainless steel foil with a thickness of 10 μm. The battery of Example 5 is named DS-5.

[0092] Example 6

[0093] The difference from Example 1 is that the passivation material in Example 6 covers the area 1 mm from the edge of the active material layer, and the battery of Example 5 is named DS-6.

[0094] Comparative Example 1

[0095] The difference from Example 1 is that in Comparative Example 1, the active material layer after drying is directly rolled to obtain a positive electrode sheet of the battery, and then the positive electrode of the battery is obtained after spot welding of the electrode lug. The battery of Comparative Example 1 is named DS-7.

[0096] Comparative Example 2

[0097] The difference from Example 1 is that in Comparative Example 2, a tape is pasted on the 1-2 cm area at the edge of the active material layer after drying. The tape used is an existing commercial BOPP film substrate tape. The battery of Comparative Example 2 is named DS-8.

[0098] Effect Example

[0099] In order to verify the performance of the battery positive electrode sheet prepared in the present application, the present application also provides an effect embodiment.

[0100] 1) The passivation region of the battery positive electrode sheets of Examples 1-6 was measured by SEM. Please refer to Table 1, which is a table of structural parameters of the battery positive electrode sheets of Examples 1-6.

[0101] Table 1 Structural parameters of the positive electrode sheets of the batteries of Examples 1-6

[0102] Experimental Group Passivation area thickness (μm) Active layer thickness (μm) Passivation layer thickness (μm) Example 1 101 95 6 Example 2 120 95 25 Example 3 130 95 35 Example 4 103 95 8 Example 5 104 95 9 Example 6 101 95 6

[0103] 2) The batteries of Examples 1-6 and Comparative Examples 1-2 were subjected to charge and discharge tests. The specific test conditions were as follows: using a blue electric test system, the positive electrode and the negative electrode were connected, and the battery was subjected to two stages of charge and discharge tests. The first stage of the charge and discharge system was: standing for 1 minute, constant current charging to 4.45V at 8mA current, then constant voltage charging at 4.45V, with a cut-off current of 2mA, then standing for 10 minutes, 8mA constant current discharge, with a cut-off voltage of 2V, and standing for 50 hours. The first stage of the test is used to form the SEI film in the battery formation and to reduce the polarization of the battery. The second stage of the charge and discharge system was: 60mA constant current charging, with a cut-off voltage of 4.45V; 4.45V constant voltage charging, with a cut-off current of 2mA; after standing for 10 minutes, 60mA constant current discharge, with a cut-off voltage of 2V, and then the second stage of the charge and discharge cycle was stopped after 800 cycles. The second stage of the test is used to test the cycle performance of the battery. The first cycle charging refers to the battery after the first test, first 60mA constant current charging to 4.45V, and then 4.45V constant voltage charging to a cut-off current of 2mA; the first cycle discharge capacity refers to the capacity discharged by the battery when the voltage is 2V at 60mA constant current. And the discharge capacity after the subsequent 800 cycles is calculated with the discharge capacity of the first cycle as the reference 100%. Please refer to Table 2, which shows the change value of the discharge capacity retention rate of the batteries of Examples 1-6 and Comparative Examples 1-2 during 800 cycles of charge and discharge.

[0104] Table 2 Cyclic performance test table of the batteries of Examples 1-6 and Comparative Examples 1-2

[0105] Battery ID Capacity retention after 800 cycles DS-1 96% DS-2 99% DS-3 99% DS-4 93% DS-5 94% DS-6 86% DS-7 83% DS-8 87%

[0106] It can be seen from the test results in Table 2 that compared with the battery composed of the positive electrode directly rolled and glued in the comparative example, the battery obtained by using the positive electrode of the battery in the embodiment of the present application has a higher capacity retention rate and the battery has better cycle performance. In comparative example 2, when the positive electrode surface is covered with tape, the negative electrode of the battery will have obvious lithium deposition after multiple cycles, thereby reducing the cycle performance and safety performance of the battery. It can be seen from Examples 1-6 that with the increase of the thickness of the passivation material, the capacity retention rate of the battery also increases, and the capacity retention rate of the battery can reach up to 99%; in the embodiment, the use of aluminum foil as a passivation material has a better effect than stainless steel foil and nickel foil. This is because aluminum has better ductility and can form a tight passivation layer on the surface of the active layer after rolling, thereby more effectively preventing the escape of lithium ions in the bad area. The positive electrode treatment method of the present application can effectively inhibit the generation of lithium dendrites at the negative electrode, thereby enhancing the cycle performance and safety performance of the battery.

[0107] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A positive electrode sheet for a battery, characterized in that: It includes a current collector and an active material layer arranged on the surface of the current collector; the active material layer includes an active area and a passivation area located on opposite sides of the active area along a first direction; the active area includes an active material; the passivation area includes a passivation material and the active material, and the passivation material includes one or more of metal aluminum, metal nickel and stainless steel; the passivation area includes an active layer arranged on the surface of the current collector and a passivation layer arranged on the surface of the active layer; the active layer includes the active material, and the passivation layer includes the passivation material; the width of the passivation area along the first direction is 3mm-2cm.

2. The positive electrode sheet of a battery as claimed in claim 1, characterized in that: The thickness of the passivation layer is 0.5 μm-95 μm.

3. The positive electrode sheet of a battery as claimed in claim 1, characterized in that: The density of the passivation layer is greater than the density of the active layer.

4. The positive electrode sheet of a battery as claimed in claim 1, characterized in that: The active layer includes a diffusion layer located on one side of the passivation layer, and the diffusion layer includes the active material and the passivation material.

5. A method for preparing a positive electrode sheet of a battery as claimed in claim 1, characterized in that: The following steps are involved: Providing a current collector, coating a surface of the current collector with an active material layer to be passivated; the active material layer to be passivated includes an active region and regions to be passivated located on opposite sides of the active region along a first direction; The passivation area is covered with a passivation material, and the active material layer to be passivated is rolled to form a passivation area to obtain the battery positive electrode sheet; the passivation material includes one or more of metal aluminum, metal nickel and stainless steel.

6. The preparation method according to claim 5, characterized in that: The passivation material includes one or more of aluminum foil, nickel foil and stainless steel foil.

7. The preparation method according to claim 6, characterized in that: The thickness of the passivation material is 2 μm-100 μm.

8. A battery, characterized in that: It comprises a positive electrode, a negative electrode, an electrolyte and a separator located between the positive electrode and the negative electrode, wherein the positive electrode comprises the battery positive electrode sheet according to any one of claims 1 to 4 or the battery positive electrode sheet obtained by the preparation method according to any one of claims 5 to 7.

Citation Information

Patent Citations

  • Pole piece, lithium ion battery, and method for manufacturing pole piece

    CN110635106A

  • layer structure for a galvanic element

    DE102014222332A1

  • Nonaqueous electrolyte secondary battery and its manufacturing method

    JP2007329077A